Recent and Upcoming Conferences - Forshaw, Peter J. (Aries, 2013)
Aries aspires to keep its readers informed about recent and upcoming conferences relevant to the study of Western esotericism, but for this, the editors are largely dependent on the information they receive. Readers are therefore invited to send Conference Programs as well as Calls for Papers and announcements of upcoming conferences to the editorial address, if possible in electronic form. In doing so, please take into account that Aries is published in the months of January and July, and that copy must have reached the editors five months in advance (i.e., August 1 and February 1 resp.).